2001
DOI: 10.1093/qjmed/94.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Renal complications of jejuno-ileal bypass for obesity

Abstract: Jejuno-ileal bypass has until recently been an accepted treatment for refractory morbid obesity. Although hyperoxaluria causing renal tract calculi is a well-recognized complication, we describe eight patients who developed significant renal failure attributable to hyperoxaluria resulting from this procedure, three requiring renal replacement therapy. We review the literature, describing 18 other cases with renal failure, the mechanisms of hyperoxaluria and its treatment. Because reversal of the bypass may res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 33 publications
0
43
0
1
Order By: Relevance
“…This leads to increased oxalate delivery to the colon where it is absorbed, while calcium is excreted along with the fat. 12 As oxalate cannot be metabolized, these larger quantities of oxalate are cleared unaltered by the kidneys thereby increasing urinary concentrations. Indeed, 47% of RYGB patients manifest hyperoxaluria compared to just 10.5% in obese controls, predisposing this population to the development of calcium oxalate type stones.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased oxalate delivery to the colon where it is absorbed, while calcium is excreted along with the fat. 12 As oxalate cannot be metabolized, these larger quantities of oxalate are cleared unaltered by the kidneys thereby increasing urinary concentrations. Indeed, 47% of RYGB patients manifest hyperoxaluria compared to just 10.5% in obese controls, predisposing this population to the development of calcium oxalate type stones.…”
Section: Discussionmentioning
confidence: 99%
“…Oxalate nephropathy is characterized by tubular crystalline deposits of calcium oxalate in kidney tissue, which lead to tubular injury, interstitial fibrosis, and progressive renal insufficiency [20]. Nasr et al [2] reported 11 cases of oxalate nephropathy after R-Y gastric bypass, in 8 patients with morbid obesity and 3 patients with gastric cancer, and renal biopsies revealed diffuse tubular degenerative changes, tubular calcium oxalate deposits, and interstitial scarring, findings which were similar to those in our renal biopsied case.…”
Section: Discussionmentioning
confidence: 99%
“…Mole et al (4) described eight cases of renal failure after JI bypass and reviewed 18 previously reported cases. Histologic evaluation was available for 17 of the 26 patients and revealed findings of tubular calcium oxalate crystals, frequently accompanied by "chronic interstitial nephritis."…”
mentioning
confidence: 99%